A developmental appraisal of the Midlands State University(MSU) relocation to Zvishavane - Marufu, Tatenda V. (Midlands State University, 2017)
This study sought to assess the developmental impacts of MSU relocation to Zvishavane community. MSU’s relocation is derived from the idea of expansion and growth of the University to obtain quality tertiary education reaching throughout Zimbabwe, as a result of adoption of multi campus concept. The study unearthed the social, economic and environmental impacts that were brought about as a result of the relocation. Whenever a developmental activity is done, there are always negative and positive impacts associated, thus the relocation of MSU to Zvishavane has impacts on both the university and the recipient town socially there are impacts on health, accommodation and education, such areas have negative impacts especially on MSU students and staff. On the economic side, positive changes were brought about on areas such infrastructure development, employment creation, the establishment of small scale business by local people, increase in scales for local large and small scale businesses. However the environment was affected negatively through increase in dumping sites